Pendampingan Administrasi Keuangan dan Pembukuan Sederhana Kelompok Usaha Mikro Kecil Menengah Sagu Boso - Sudirman, Muh Sajjaj; Jasmin, Jasmin; Pattimura, Muhammad Fatwa; Hasnidar, Hasnidar (Prioritas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Assistance in managing financial administration and simple bookkeeping is a strategic effort to strengthen financial management capabilities in micro, small and medium enterprise (MSME) groups. The purpose of this activity is to empower the Sago Boso MSME group in understanding the importance of proper financial management and an effective financial administration system in order to support the government's steps in overcoming unemployment and opening up as many jobs as possible. The method applied in this community service program is participatory action research (PAR) which prioritizes a collaborative and empowerment-oriented approach. This method aims to create relevant and sustainable social change through a series of participatory steps, namely problem identification, action planning, implementation, evaluation and reflection. The results of this community service show an increase in the understanding and ability of the sagu boso MSME group to record financial transactions and prepare simple correct financial reports. This assistance is expected to be sustainable and become an empowerment model that can be applied to other MSME sectors to support local economic strengthening and job creation. Kata kunci: Financial administration; Simple bookkeeping; Micro Small Medium Enterprises (MSME)